MAKING OF JFG (JUMANJI FOR GRAMMAR) BOARD GAME TO LEARN GRAMMAR FOR UNIVERSITY STUDENTS - Hadi Wijaya; Diah Paramita Sari (INOVISH JOURNAL, 2016)
Abstract: There are four skills in learning English that should be mastered by students such as listening, speaking, reading and writing. To support those four skills, students should master in grammar. The basic of grammar in learning English is Tenses. One of way in learning grammar is through games. Jumanji is one of games which have many advantages. JFG (Jumanji for Grammar) was adopted by Jumanji that purposed to learn grammar. The purpose of this study is to make JFG board game to learn grammar for university students. The idea of this project comes up because there is no a JFG board game to learn grammar for the university students in Bengkalis. The result of this study was a set of JFG Board Game as medium to learn of grammar especially in tenses. This game consists of a dice, board of jumanji, five sets of question cards and four pawns with different colors. By using this game, the student can learn grammar in a more interesting and effective way.Keywords: JFG (Jumanji for Grammar) Board Game, Grammar, Students in University.